Revê-la Adrift: Rebirths - Oleinik, Tatiane Maira (Revista do Colóquio, 2026)
This visual essay is positioned as an unfolding of my research Revê-la (2023), investigating the body as an unstable field of passage. Its objective is to understand how performative reactivation produces variations through gestures of removal, melting, and recomposition. The methodological approach articulates reperformance, process-based practice, and photographic documentation as cuts of the event. As results, wax emerges as a material of impermanence, and the repeated gesture as a producer of difference. It is concluded that the work displaces the notion of origin toward continuity as transformation, affirming the process as an open field.
Keywords: Body; art of performance; Photography